Evidence that PKCα inhibition in Dalton's Lymphoma cells augments cell cycle arrest and mitochondrial-dependent apoptosis. (February 2022) - Singh, Rishi Kant; Verma, Praveen Kumar; Kumar, Sandeep; Shukla, Alok; Kumar, Naveen; Kumar, Sanjay; Acharya, Arbind
Graphical abstract: Highlights: PKCα has been implicated in cell death, cell survival and myriad cellular functions. Inhibition of PKCα resulted in mitochondrial-dependent apoptosis in Daltons Lymphoma Cells. DL cells treated with PKCα inhibitors resulted in G1 phase cell cycle arrest and growth retardation. Abstract: Protein kinase Cα (PKCα), belonging to ser/thr protein kinase, perform various biological functions. Overexpression of PKCα has been observed in multiple human malignancies including lymphoma. However, the molecular pathogenesis and involvement of PKCα in Non-Hodgkin lymphoma (NHL) are not clearly understood. Hence, deciphering the role of PKCα in NHL management may provide a better therapeutic option. In the present study, we used selective pharmacological inhibitors Gö6976 and Ro320432 that potentially inhibit PKCα-mediated signaling in DL cells, resulting in the inhibition of cell growth and mitochondrial-dependent apoptosis. PKCα inhibition by these inhibitors also displays cell cycle arrest at the G1 phase and causes growth retardation of DL cells. Our results extended the mechanism of PKCα in NHL, and provided potential implications for its therapy.